Role of Small Intestine and Gut Microbiome in Plant-Based Oral Tolerance for Hemophilia - Kumar, Sandeep R. P.; Wang, Xiaomei; Avuthu, Nagavardhini; Bertolini, Thais B.; Terhorst, Cox; Guda, Chittibabu; Daniell, Henry; Herzog, Roland W. (Frontiers in Immunology, 2020)
Fusion proteins, which consist of factor VIII or factor IX and the transmucosal carrier cholera toxin subunit B, expressed in chloroplasts and bioencapsulated within plant cells, initiate tolerogenic immune responses in the intestine when administered orally. This approach induces regulatory T cells (Treg), which suppress inhibitory antibody formation directed at hemophilia proteins induced by intravenous replacement therapy in hemophilia A and B mice. Further analyses of Treg CD4+ lymphocyte sub-populations in hemophilia B mice reveal a marked increase in the frequency of CD4+CD25-FoxP3-LAP+ T cells in the lamina propria of the small but not large intestine. By contrast, no changes in frequencies of CD4+CD25+FoxP3+ T cells were observed. Here we demonstrate that, surprisingly, the adoptive transfer of very small numbers of CD4+CD25-LAP+ Treg isolated from the spleen of tolerized mice significantly suppress antibodies directed against FIX. By contrast, equal numbers of splenic CD4+CD25+ T cells do not have an effect on antibody formation. Thus, tolerance induction by oral delivery of antigens bioencapsulated in plant cells occurs via the unique immune system of the small intestine and that suppression of antibody formation is primarily carried out by induced latency-associated peptide (LAP) expressing Treg. The observation that CD4+CD25-LAP+ Treg migrate to the spleen are useful for the design of clinical protocols.